2007
DOI: 10.1007/s11130-007-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumption of Selenium Enriched Rye/Wheat Sourdough Bread on the Body’s Selenium Status

Abstract: The potential of selenium-enriched rye/wheat sourdough bread as a route for supplementing dietary selenium intakes is reported. In addition to their normal diets, 24 female volunteers (24 to 25 years old) were fed either selenium-enriched bread or non-enriched bread each day (68.02 and 0.84 microg selenium day(-1) respectively) for 4 weeks. The chemical form of the selenium in the bread had been characterised using HPLC-ICP-MS, which showed that 42% of the extractable selenium was present as selenomethionine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Selenium (Se) analyses were carried out by Inductively Coupled Plasma Mass Spectrometry (ICPMS) according to Bryszewska et al (22) on samples digested with nitric acid and finished with hydrochloric acid. Finally, moisture, ash, protein, and fat were evaluated according to the standard AACC methods (23).…”
Section: Bread Compositionmentioning
confidence: 99%
“…Selenium (Se) analyses were carried out by Inductively Coupled Plasma Mass Spectrometry (ICPMS) according to Bryszewska et al (22) on samples digested with nitric acid and finished with hydrochloric acid. Finally, moisture, ash, protein, and fat were evaluated according to the standard AACC methods (23).…”
Section: Bread Compositionmentioning
confidence: 99%
“…A decrease in the salt content of bread is possible by replacing partially the salt content by other salts, mainly of potassium [4] without detrimental effects in terms of both technology and sensory acceptance [5]. Healthy and organoleptic features of bread can be additionally improved through sourdough fermentation by lactic acid bacteria (LAB) [6,7]. Recent studies have shown that LAB metabolism may produce new nutritionally bioactive compounds with antihypertensive activity such as γ-aminobutyric acid (GABA), the main inhibitory neurotransmitter in the mammalian nervous system, that is well known for lowering BP and its diuretic and tranquilizer effects [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The Se level in the soils of many European countries generally is low (Rayman 2000, Oldfield 2002). Moreover, the significant impact on reducing Se content in European food was the substitution of North American wheat imports from produce grown within Europe (Bryszewska et al 2007). The studies performed in Poland, based on Se concentrations in cow's milk and partly on Se concentrations in grass and in livers of hares, showed that about 75 % of Poland is Se-deficient and only 25 % is adequate, when considering the nutritional requirements of humans and animals Pilecki 2000, Dębski et al 2001).…”
Section: Introductionmentioning
confidence: 99%